Clinical findings, early endoscopy, and multivariate analysis in patients bleeding from the upper gastrointestinal tract. Issue 6081 (23rd July 1977) - Morgan, A G; McAdam, W A; Walmsley, G L; Jessop, A; Horrocks, J C; de Dombal, F T
Abstract : A simple system has been developed to identify patients with upper gastrointestinal tract haemorrhage who run a high risk of continued bleeding or rebleeding. The system is based on six items of patient data available at or soon after arrival in hospital. It was evaluated in a prospective study of 66 patients with upper gastrointestinal tract haemorrhage. Over half of the patients classified by the system into a high-risk category either continued bleeding or rebled after apparent cessation (as against one out of 33 patients in the low-risk category). The high-rish group also had a higher mortality (21%) than those in the low-risk group (nil). The addition or subtraction of early endoscopic findings made little difference to the accuracy of prognosis.